Wonderment of the true nature - Mariapan, Manohar (University Putra Malaysia, 2012)
Living fruit plants depicted beyond their mundane meanings are provocative revelations that people tend to appreciate. As human beings we don’t know what we don’t know! The secrets about plants revealed through creatively written articles in this chapter give the reader an opportunity to relate life experiences with plants that are more meaningful. Being able to see beyond ones normal capabilities can give us enduring satisfaction. Plant characteristics are not just seen as another botanical jargon but as amazing meaningful revelations that one can appreciate both physically and cognitively. The revealing insights into the secrets behind various plant morphologies and processes are wonderments of the true nature of things as interpreted by the respective scientists. The stories are made relevant to the audience with their,sometimes,mind boggling depiction of messages opposing our basic belief about plants.